(untitled) (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: The current study was carried out to investigate the toxico-pathological and teratogenic effects of in-ovo administration of fungal-derived extracts of Ochratoxin (OT) and Aflatoxin (AF) and Bacillus cereus isolated from poultry feeds. Materials and Methods: Fertilized chicken eggs were divided into seven groups: control, sham control (normal saline), OT (600 ppb), AF (400 ppb), OT+AF (600 + 400 ppb), B. cereus (1 × 10⁸ CFU), and OT + AF + B. cereus (600 + 400 ppb + 1×10⁸ CFU). The extracts of each fungus and B. cereus were injected through the Chorioallantoic membrane route into 9-day-old embryos (216 h). The study evaluated embryonic mortality, hatchability, body weight, relative organ weights, and gross lesions. Morphometric alterations, including crown-to-rump, shank, head, and limb lengths, were measured. Results: Variable degrees of mortality and reduced hatchability were observed across treatment groups. Embryonic mortality was highest in combination groups F and G at 24 and 96 h, whereas the OT group showed the highest mortality at 48 and 72 h. Body weights and all morphometric parameters decreased significantly in the treated groups compared to the control groups. Teratogenic effects included curling, dwarfism, hemorrhages, stunted growth, feather loss, anophthalmia, malformed bills, twisted necks, abdominal hernias, and malformed fingers and limb buds. Conclusion: These findings suggest that inoculation of OT, AF, and B. cereus, individually or in combination, exerts severe teratogenic and embryotoxic effects, resulting in high embryonic mortality and developmental malformations. J. Adv. Vet. Anim. Res., 12(4): 1370–1378, December 2025 http://doi.org/10.5455/javar.2025.l997